MARINE RENEWABLE ENERGY, THE LAW OF THE SEA AND THE MARINE ENVIRONMENT: AN INDONESIAN PERSPECTIVE - Gusman Siswandi (Padjadjaran Journal of International Law, 2017)
ABSTRACTAccording to the report of the Secretary-General of the United Nations, there are at least three benefits of marine renewable energy. From an environmental perspective, the utilization of marine renewable energy could reduce dependency upon conventional energy sources, especially the non-renewable ones. From an economic perspective, the renewable energy projects have developed significantly both in developed and developing countries. It was estimated that global investments in the renewable energy sector increased by 32% in 2010, reaching the total figure of $2.11 billion. Although there have not been any statistics available for marine renewable energy, this figure could provide an indication for the prospects of marine renewable energy in the future. This article aims to identify and to analyze legal aspects related to the utilization of marine renewable energy in Indonesia, particularly in the contexts of the law of the sea and the marine environment. Since marine renewable energy in Indonesia is still developing, it is necessary to ensure that all activities pertaining to the utilization of marine renewable energy resources are conducted in accordance with prevailing laws and regulations. In this regard, the 1982 United Nations Convention on the Law of the Sea (UNCLOS) is one of the main legal instruments that need to be considered by coastal States in utilizing marine renewable energy. This study finds that the current laws and policy in Indonesia are still inadequate to regulate the development of marine renewable energy. The National Energy Policy only provides a broad and general policy on renewable energy sources and does not cover a particular strategy on marine renewable energy. Thus, the Indonesian Government needs to establish a specific policy on marine renewable energy as well as specific laws and regulations to address the environmental impacts that may result from marine renewable energy activities. Keywords: marine renewable energy, law of the sea, marine energy, indonesian perspective. ABSTRAKBerdasarkan laporan dari Sekjen PBB, sekurang-kurangnya terdapat tiga keuntungan dari energi laut terbarukan. Dari perspektif lingkungan, pemanfaatan energi laut terbarukan dapat mengurangi ketergantungan terhadap energi konvensional, khususnya yang tidak terbarukan. Dari perspektif ekonomi, proyek energi terbarukan telah berkembang cukup signifikan, baik di negara berkembang maupun negara maju. Secara global, diperkirakan telah terdapat kenaikan investasi sebesar 32% di tahun 2010, hingga mencapai 2.11 miliar US Dolar. Meskipun belum ada statistik yang pasti, akan tetapiangka tersebut sudah menggambarkan prospek perkembangan energi terbarukan di masa yang akan datang. Artikel ini bertujuan untuk menganailisa aspek hukum yang berkaitan dengan pemanfaatan energi laut terbarukan di Indonesia, khususnya dalam konteks hukum laut dan lingkungan laut. Sejak energi laut terbarukan berkembang di Indonesia berkembang, sangatlah diperlukan agar pengeturan kegiatan tersebut sesuai dengan peraturan perundang-undangan. Berkenaan dengan ini, Konvensi Hukum Laut 1982 adalah salah satu dari intrumen hukum yang harus diperhatikan oleh negara pantai dalam menjalankan kegiatan pemanfaatan energi laut terbarukan. Kebijakan Energi Nasional hanya menyediakan kebijakan nasional yang sifatnya umum dalam pemanfaatan energi laut terbarukan. Dengan demikian Indonesia perlu membentuk kebijakan yang lebih spesifik berkenaan dengan pemanfaatan energi laut terbarukan, khususnya dampak lingkungan terhadap pemanfaatan energi laut terbarukan. Kata kunci: energi laut terbarukan, hukum laut, energi laut, sudut pandang indonesia